2016
DOI: 10.1177/1744806916654146
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of methadone as a β-arrestin-biased μ-opioid receptor agonist

Abstract: BackgroundMethadone is a unique µ-opioid receptor agonist. Although several researchers have insisted that the pharmacological effects of methadone are mediated through the blockade of NMDA receptor, the underlying mechanism by which methadone exerts its distinct pharmacological effects compared to those of other µ-opioid receptor agonists is still controversial. In the present study, we further investigated the pharmacological profile of methadone compared to those of fentanyl and morphine as measured mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 32 publications
(44 reference statements)
0
11
0
1
Order By: Relevance
“…We used a noneffective dose of NTX that did not have a significant impact on seizure threshold . Moreover, methadone has high affinity for µ‐opioid receptors . Therefore, it may be concluded that one of the possible interactions between the application of methadone along with the noneffective dose of NTX is mediated via the µ‐opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…We used a noneffective dose of NTX that did not have a significant impact on seizure threshold . Moreover, methadone has high affinity for µ‐opioid receptors . Therefore, it may be concluded that one of the possible interactions between the application of methadone along with the noneffective dose of NTX is mediated via the µ‐opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…For example unlike opioids such as morphine, fentanyl and methadone, buprenorphine does not recruit β-arrestin to the receptor (86) and as described above buprenorphine has been reported to be devoid of immunosuppressive properties. Indeed morphine is a balanced agonist, and its ability to recruit arrestin after receptor binding is lower than that of fentanyl or methadone that have been suggested to be a β-arrestin biased compounds (85,87). However, morphine and fentanyl have comparable immunosuppressive activity, while methadone is a weaker immunomodulator and therefore the concept of biased agonist is not sufficient to explain differences.…”
Section: Discussionmentioning
confidence: 99%
“…TLR signaling and respective downstream effects are modulated by β‐arrestin proteins, for example, by forming a complex with TRAF6, eventually inhibiting NfĸB activity . Since d , l ‐methadone (but not morphine) is known to be a potent (∼1 µM) β‐arrestin‐recruiting opioid receptor desensitizer, the negatively regulating impact of ß‐arrestin on NfĸB functionality might be abolished by chronic opioid receptor activation. In other words, if β‐arrestin is constantly distracted from the NfĸB complex, d , l ‐methadone could indirectly influence the pro‐apoptotic NfĸB pathway by trapping β‐arrestin proteins to opioid receptors.…”
Section: Pharmacological Basis Of Antineoplastic Dl‐methadone or Othmentioning
confidence: 99%